Dravya Guna – Backbone Of Clinical Practice In Ayurveda - Gangawa, Vd Anant; Rath, Sudipt (International Research Journal of Ayurveda & Yoga, 2021)
Dravyaguna is a branch of Ayurveda which deals with the study of properties of plants and its effect on human body. Rasapanchaka is the speciality of Ayurveda which is explained on the principles of Panchamahabhoot which shows the systematic way to understand Pharmacodynamics and pharmacokinetics of the drug which ultimately help in the selection of drug for a particular disease and for the preventive measures also. It is a science which include all the principles which is important for the selection of a drug that leads to the success in the treatment, so it is fair to say that Dravyaguna is the backbone for the clinical practice of Ayurveda.